Association of serum orosomucoid with 30-min plasma glucose and glucose excursion during oral glucose tolerance tests in non-obese young Japanese women. Issue 1 (29th April 2018) - Tsuboi, Ayaka; Minato, Satomi; Yano, Megumu; Takeuchi, Mika; Kitaoka, Kaori; Kurata, Miki; Yoshino, Gen; Wu, Bin; Kazumi, Tsutomu; Fukuo, Keisuke
Abstract : Objective: Inflammatory markers are elevated in insulin resistance (IR) and diabetes. We tested whether serum orosomucoid (ORM) is associated with postload glucose, β-cell dysfunction and IR inferred from plasma insulin kinetics during a 75 g oral glucose tolerance test (OGTT). Research design and methods: 75 g OGTTs were performed with multiple postload glucose and insulin measurements over a 30–120 min period in 168 non-obese Japanese women (aged 18–24 years). OGTT responses, serum adiponectin and high-sensitivity C reactive protein (hsCRP) were cross-sectionally analyzed by analysis of variance and then Bonferroni's multiple comparison procedure. Stepwise multivariate linear regression analyses were used to identify most important determinants of ORM. Results: Of 168 women, 161 had normal glucose tolerance. Postload glucose levels and the area under the glucose curve (AUCg) increased in a stepwise fashion from the first through the third ORM tertile. In contrast, there was no or modest, if any, association with fat mass index, trunk/leg fat ratio, adiponectin, hsCRP, postload insulinemia, the Matsuda index and homeostasis model assessment IR. In multivariable models, which incorporated the insulinogenic index, the Matsuda index and HOMA-IR, 30 min glucose (standardized β: 0.517) and AUCg (standardized β: 0.495) explained 92.8% of ORM variations. Conclusions: Elevated circulating orosomucoid was associated with elevated 30 min glucose and glucose excursion in non-obese young Japanese women independently of adiposity, IR, insulin secretion, adiponectin and other investigated markers of inflammation. Although further research is needed, these results may suggest a clue to identify novel pathways that may have utility in monitoring dysglycemia within normal glucose tolerance.